What to feed your baby & toddler : a month-by-month guide to support your child's health & development - Avena, Nicole M., 1978-; Ferreira, Charity (Ten Speed Press, 2018)
"A science-based manual for feeding babies exactly what they need to hit physical and intellectual milestones from 6 to 24 months, with 60 recipes. World-renowned research neuroscientist, nutrition expert, and author of What to Eat When You're Pregnant Dr. Nicole M. Avena presents an essential guide for new parents on feeding babies during their critical first two years. Answering common questions about picky eaters, food allergies, diversifying baby's appetite, eating out or on the go, feeding baby at daycare or when with another caregiver, and food safety, this comprehensive guide offers easy monthly meal plans and baby-friendly, nutrient-rich recipes designed to support your baby's developmental milestones"--